Farmers' Attitudes toward the Future of Direct Payments: An Empirical Study from Germany - Sabrina Bethge; Sebastian Lakner (German Journal of Agricultural Economics (GJAE), 2023)
The new Common Agricultural Policy (CAP) reform has met with large-scale protests from farmers throughout Europe, intending to change one of the most controversial components: direct payments. We analyze German farmers' attitudes and understanding of direct payments. The study employs a survey of 435 farmers collected from January to February 2021. Using cluster analysis and quantitative content analysis, we identified three distinct groups: (1) The "Independents" (43.7%) are entrepreneurs and have a competitive mindset. They would prefer to abolish direct payments associated with more freedom from policy conditions. (2) The "Conservatives" (27.0%) advocate an income policy based on direct payments, and they reject higher environmental standards. (3) The "Environmentalists" (30.3%) emphasize a pronounced environmental awareness, fa-voring an environmentally performance-based approach. The results show that policies are often perceived differently than they are intentionally designed. Improving the effectiveness of the policy measure requires sufficient information about the CAP's objectives for farmers, focusing on more transparent communication strategies. From a policy perspective, a more differentiated design of policy instruments and longer transformation periods are needed to engage farmers in policy change.
Keywords: 330; direct payments; farmers' attitudes; Common Agricultural Policy; factor analysis; cluster analysis